The study on the perception of employees towards facial based discrimination in workplace / Halimatu Saadiah Amat and Nooreffariza Awang Muslaini - Amat, Halimatu Saadiah; Awang Muslaini, Nooreffariza (2011)
To be human is to discriminate" even it is hard to admit but it has been proved by many scholars that discrimination do happen in this world long time ago. According to Longman dictionary, discrimination is treatment or consideration of, or making a distinction in favor of or against, a person or thing based on the group, class, or category to which that person or thing belongs rather than on individual merit. The discrimination is varied; it can be racial, religious, wealth, ethnic, sexual and also physical appearance. For this study the physical appearance will be focused but only the facial criterion is the types of physical appearance discrimination that will be study on.